Manipulative Messages in 'Ice Cold: Murder, Coffee, and Jessica Wongso': A Case Study of a Netflix Documentary - Muhammad Qadaruddin; Nining Artianasari; Fikruzzaman Saleh; Jalihah Md Shah (INJECT (Interdisciplinary Journal of Communication), 2024)
This research examines the presence and implications of manipulative messages in the Netflix documentary "Ice Cold: Murder, Coffee, and Jessica Wongso." By using framing analysis on the film, this research highlights how these messages shape the audience's perception and understanding of the events. The filmmaker's stance on the case attempts to present both sides of the case fairly, allowing the audience to draw their own conclusions. This film portrays Jessica with nuance to consider the possibility that Jessica is both a perpetrator and a victim of the system and excessive media coverage. Furthermore, this research explores the cultural and societal contexts that have influenced the production of the documentary film, revealing how these factors contribute to the overall message. These findings indicate that the film director presents a perspective that attempts to view Jessica as a victim of media pressure and a legal process deemed unfair. Interviews with legal experts, Jessica's friends, and scenes showing the weaknesses and inconsistencies of the presented evidence also contribute to the narrative that Jessica might be innocent and instead a victim of unbalanced media framing. Until the year 2024, Jessica was declared free. This release marks a long-awaited victory for justice. This documentary film plays a significant role in raising public and judicial system awareness about the potential injustices that can befall an individual. This research is not merely entertainment, but rather an important medium that can contribute to voicing injustice and striving for justice in complex and controversial cases.